Does workplace ostracismce lead to counterproductive work behavior in healthcare employees: the role of transactional and relational psychological contract breach - Muhammad Rizwan Sabir; Muhammad Bilal Majid; Muhammad Zia Aslam; Abdul Rehman; Sumaira Rehman (Cogent Business & Management, 2024)
With the presence of negative organizational behaviors, not only is the employee's productivity and job satisfaction affected, but the entire organizational performance of employees also declines. Workplace ostracism affects employees' psychological well-being by fostering exhaustion of their emotional, psychological, and material resources, significantly influencing counterproductive work behavior. The present research also addresses the emerging negative workplace behaviors by studying the mediation of transactional and relational psychological contract breaches. The research has adopted a `quantitative research design' followed by a survey approach to collect data from Pakistan's healthcare sector employees. 420 questionnaires were disbursed among employees, of which 350 were received back, and 332 questionnaires were finalized after data cleaning and screening. Smart-Pls was used to analyze data and assess the association among different variables. Different tests were performed including the descriptive summary, validity (convergent and discriminant), model fitness and path analysis. Results indicated that WOC significantly impacts CWB. RPCB also significantly influences the CWB. TPCB insignificantly effects CWB and WOC significantly influences RPCB and TPCB. Mediation of TPS has been insignificant, whereas the mediation of RPS has resulted as significant. The present research holds considerable theoretical and practical importance as it provides practical insights to the managerial bodies of the healthcare sector in Pakistan to make strategies for vanishing such counterproductive work behaviors of employees that damage the morale and mental peace of other workers. The limitations of this research have also been addressed in the last section.This research examined how workplace ostracism leads to counterproductive work behaviors in healthcare employees in Pakistan, mediated by relational and transactional psychological contract breaches. A quantitative survey collected data from 350 employees, with 332 used after screening. Analysis with SmartPLS tested associations between workplace ostracism, contract breaches, and counterproductive behavior. Results showed workplace ostracism significantly impacted counterproductive behavior. Relational contract breach mediated this relationship, while transactional breach did not. The findings contribute theoretically by linking workplace ostracism to counterproductive behaviors through psychological contract violations. Practically, they suggest reducing ostracism and relational contract breaches to curb counterproductive behaviors in healthcare organizations. Limitations include the cross-sectional design and sampling from one sector in one region. Further research could use experimental, longitudinal approaches and more diverse samples. Overall, this highlights the need to address emerging negative behaviors like ostracism to maintain positive psychological contracts and productive work environments.
Keywords: 650; Workplace ostracism; counterproductive work behavior; psychological contract breach; transactional contract breach